2022
DOI: 10.2147/jir.s358470
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ferroptosis in Fibrotic Diseases

Abstract: Ferroptosis is a unique and pervasive form of regulated cell death driven by iron-dependent phospholipid peroxidation. It results from disturbed cellular metabolism and imbalanced redox homeostasis and is regulated by various cellular metabolic pathways. Recent preclinical studies have revealed that ferroptosis may be an attractive therapeutic target in fibrotic diseases, such as liver fibrosis, pulmonary fibrosis, kidney fibrosis, and myocardial fibrosis. This review summarizes the latest knowledge on the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“… 510 Evidence has shown that ferroptosis is involved in the pathogenesis of kidney fibrosis. 432 , 487 , 511 516 A recent study also showed the role of epigenetic regulation of ferroptosis by deacetylation in kidney fibrosis. Sirtuin 1-mediated p53 deacetylation was found to attenuate calcium oxalate deposition-induced renal fibrosis by suppressing ferroptosis.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 97%
“… 510 Evidence has shown that ferroptosis is involved in the pathogenesis of kidney fibrosis. 432 , 487 , 511 516 A recent study also showed the role of epigenetic regulation of ferroptosis by deacetylation in kidney fibrosis. Sirtuin 1-mediated p53 deacetylation was found to attenuate calcium oxalate deposition-induced renal fibrosis by suppressing ferroptosis.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 97%
“…It is well-established that specific types of RCD, including ferroptosis, can activate the immune system and initiate an inflammatory reaction [156]. Therefore, ferroptosis induction has been implicated in the pathogenesis of fibrogenesis in diverse organs, including the liver, kidney, myocardium, gastrointestinal system, salivary glands, pancreas, prostate, and lung [157][158][159]. The ferroptotic mechanisms underlying the development of fibrosis in these organs have been thoroughly revised elsewhere [157,159].…”
Section: Adverse Events Of Ferroptosis Inducers As Radiosensitizersmentioning
confidence: 99%
“…Therefore, ferroptosis induction has been implicated in the pathogenesis of fibrogenesis in diverse organs, including the liver, kidney, myocardium, gastrointestinal system, salivary glands, pancreas, prostate, and lung [157][158][159]. The ferroptotic mechanisms underlying the development of fibrosis in these organs have been thoroughly revised elsewhere [157,159]. Albeit ferroptosis induction has been extensively linked to fibrosis, knowledge about the role of ferroptosis in RIF and acute tissue toxicity is still limited.…”
Section: Adverse Events Of Ferroptosis Inducers As Radiosensitizersmentioning
confidence: 99%
“…A potential strategy to overcome this challenge is targeting common mechanisms and core pathways with central pathophysiological relevance in different pathological alterations in AKI to CKD [50]. Ferroptosis plays a vital role in regulating various cellular processes, such as inflammation [51], mitochondrial dysfunction [52], fibrosis [53], and renal cell regeneration [54], and has been considered a promising therapeutic target in the progression of AKI to CKD.…”
Section: The Role Of Ferroptosis In the Pathogenesis Of Aki To Ckd Pr...mentioning
confidence: 99%